Desempenho de Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae), submetido a inseticidas e fungicidas em dois hospedeiros1 - Santos, Vinícius Pereira Dos; Pratissoli, Dirceu; Paes, João Paulo Pereira [UNESP]; Fragoso, Débora Ferreira Melo; Carvalho, José Romário De (Universidade Federal de Viçosa, 2016)
This study aimed to evaluate the influence of different insecticides and fungicides to Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) in different hosts. The tests were performed on adults of T. pretiosum in host Anagasta kuehniella (Zeller, 1879) (Lepidoptera: Pyralidae) and Helicoverpa zea (Boddie, 1850) (Lepidoptera: Noctuidae). The results showed that the pesticides studied had different effects on T. pretiosum depending on the host. The insecticides IMIDACLORIPRIDO + BETA-CYFLUTHRIN and METHOMYL were the most aggressive reducing parasitism of adult T. pretiossum in both hosts, whereas for fungicides, DIMETOMORPH + MANCOZEB and MANCOZEB were the most influential. From the results it is concluded that the host can influence the selectivity tests of insecticides and fungicides on parasitoids of the genus Trichogramma, considering, T. pretiosum was more susceptible to the insecticide METHOMYL and ACIBENZOLAR-S-METHYL when created in A. kuehniella and the fungicide MANCOZEB + DIMETOMORPH created when H. zea. There were no significant reductions in emergency percentage of descendants when fungicides were applied.

Este trabalho teve como objetivo avaliar a influência de diferentes inseticidas e fungicidas, sobre Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae), em diferentes hospedeiros. Os testes foram realizados com adultos de T. pretiosum nos hospedeiros Anagasta kuehniella (Zeller, 1879) (Lepidoptera: Pyralidae) e Helicoverpa zea (Boddie, 1850) (Lepidoptera: Noctuidae). Os resultados mostraram que os agrotóxicos estudados tiveram efeitos diferentes sobre T. pretiosum, em função do hospedeiro. Os inseticidas IMIDACLORIPRIDO + BETA-CIFLUTRINA e METHOMYL foram os mais agressivos, reduzindo o parasitismo dos adultos de T. pretiosum em ambos os hospedeiros, enquanto, para os fungicidas, DIMETOMORPH + MANCOZEB e MANCOZEB foram os mais influentes. Diante dos resultados, conclui-se que o hospedeiro pode influenciar na ação seletiva dos inseticidas e fungicidas sobre parasitoides do gênero Trichogramma, visto que T. pretiosum foi mais susceptível ao inseticida METHOMYL e ao ACIBENZOLAR-S-METHYL, quando criado em A. kuehniella, e ao fungicida DIMETOMORPH + MANCOZEB, quando criado em H. zea. Não houve reduções expressivas dos percentuais de emergência dos descendentes, quando os fungicidas foram aplicados.
Performance of Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) submitted to insecticides and fungicides in two hosts
Keywords: Parasitoid; Pesticides; Plant management; Alternative hosts; Parasitoide; Agrotóxicos; Manejo Fitossanitário; Hospedeiros alternativos